TENDENCIES OF TRADE DEVELOPMENT IN THE TRANSFORMATION ECONOMY OF UKRAINE - Korolkov, Ivan; Shymko, Olha (Journal of European Economy, 2018)
The paper is devoted to topical problems of trade development in the conditions of economic reforms. The attention is focused on the issues of state trade regulation effectiveness and the shortcomings of actual methods of compiling statistics.